A non-fluorine positive electrode binder and its preparation method and application

By developing a fluorine-free positive electrode binder, the gel phenomenon of high-nickel ternary positive electrode material slurry is avoided by using specific polymer combinations, the problems of environmental pollution and supply are solved, and the performance of positive electrode sheets is improved and stability.

CN115881968BActive Publication Date: 2025-02-11SHENZHEN HAODYNE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310060781.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-18
Publication Date
2025-02-11
Estimated Expiration
2043-01-18

AI Technical Summary

Technical Problem

In the prior art, the slurry of high-nickel ternary cathode material is prone to gelation, and the use of fluorine chemical material PVDF has problems of environmental pollution and supply shortage.

Method used

Develop a non-fluorine positive electrode binder, by using a combination of a fluorine-free first polymer and a second polymer, the HF deletion and cross-linking of the PVDF molecular chain in a strong alkaline environment was avoided, thus solving the problem of Problems with slurry gel.

Benefits of technology

It is achieved to avoid slurry gel in the high-nickel ternary positive electrode system, improve the adhesion and stability of the positive electrode sheet, reduce production costs, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004061195210000031
    Figure BDA0004061195210000031
  • Figure BDA0004061195210000101
    Figure BDA0004061195210000101
  • Figure BDA0004061195210000102
    Figure BDA0004061195210000102
Patent Text Reader

Abstract

The present invention provides a non-fluorine positive electrode binder and a preparation method and application thereof, wherein the non-fluorine positive electrode binder comprises a combination of a first polymer and a second polymer, wherein the polymerized monomers of the first polymer include, by mass, 80-90 parts of acrylonitrile, 5-10 parts of a first acrylate monomer, and 1-5 parts of a first functional monomer; and the polymerized monomers of the second polymer include, by mass, 60-75 parts of a second acrylate monomer, 10-15 parts of acrylonitrile, 10-20 parts of a vinyl hydrocarbon monomer, and 1-5 parts of a second functional monomer. The non-fluorine positive electrode binder does not contain any fluorine element, completely solves the slurry gel problem of PVDF applied to high-nickel ternary, and is low-cost and environmentally friendly. At the same time, the non-fluorine positive electrode binder has excellent dispersibility, bonding strength and flexibility, so that the positive electrode sheet containing it has excellent bonding strength and stability, and the manufactured lithium-ion battery has better performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a non-fluorine positive electrode binder and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are an important branch of the new energy industry, with the characteristics of light weight, high energy density, low self-discharge, long life, high discharge power and good environmental protection. They have attracted much attention in recent years and are widely used in electronic equipment, communication equipment, electric vehicles and other recycling energy systems. Lithium-ion batteries are generally composed of positive electrodes, negative electrodes, diaphragms and electrolytes. The performance of positive and negative electrodes directly affects the quality of lithium-ion batteries.

[0003] The positive electrode is usually made of metal as a substrate, and the positive electrode active material is attached to the metal surface by a binder. The current commercial positive electrode binder is polyvinylidene fluoride (PVDF). PVDF has excellent performance in electrochemical stability, adhesion, lithium ion migration ability and thermal stability, and can basically meet the needs of positive electrode binders for lithium-ion batteries. However, with the increasing requirements for the energy density of lithium-ion batteries in the industry, high-nickel ternary positive electrode materials have become a development trend. The higher the nickel content in lithium-nickel-cobalt-manganese-oxygen, the stronger the alkalinity of the material. Since the PVDF molecular chain will remove the HF molecule in a strong alkaline environment and form continuous double bonds on the molecular chain, and there may be double bond breaks and cross-linking with other molecular chains, the slurry is prone to gelation, which affects normal batching, coating and subsequent processes. In addition, PVDF is a fluorine chemical material with high production costs and serious environmental pollution. In addition, the global resources of raw materials for producing PVDF are limited, resulting in a tight supply of PVDF. Therefore, the development of new positive electrode binders and positive electrode slurries is an important research topic in the industry.

[0004] In order to improve the gelation phenomenon of high-nickel ternary positive electrode material slurry, the existing method is to obtain modified PVDF by adding a small amount of special monomers, such as trifluorochloroethylene, hexafluoropropylene, tetrafluoroethylene, vinyl monomers containing carboxyl groups, olefin monomers capable of producing carboxyl groups, etc., during the polymerization of PVDF, thereby reducing the chain reaction of PVDF molecular chain de-HF. For example, CN109713306A discloses a binder and positive electrode slurry, wherein the binder includes a blend of tetrafluoroethylene-vinylidene fluoride copolymer (TFE-VDF copolymer) and polyvinylidene fluoride. Since TFE is tetrafluoro, the probability of de-HF is reduced, thereby reducing the degree of gelation of the binder, which can weaken the gelation problem of lithium ion positive electrode slurry during mixing to a certain extent. CN115188963A discloses a binder and a positive electrode sheet and a battery comprising the binder. The binder comprises at least one graft copolymer, which is prepared by graft copolymerization of a vinyl monomer and a fluorine-containing monomer; the vinyl monomer comprises vinylidene fluoride and an unsaturated organic acid monomer containing a vinyl group, such as an unsaturated carboxylic acid monomer containing a vinyl group, an unsaturated boric acid monomer containing a vinyl group, or an unsaturated sulfonic acid monomer containing a vinyl group; the fluorine-containing monomer is grafted onto the side chain of vinylidene fluoride; the binder has excellent bonding strength, and the introduction of the fluorine-containing side chain can protect the H atoms on the main chain, avoid the occurrence of physical crosslinking, and improve the stability of the slurry. CN115286730A discloses a vinylidene fluoride copolymer, which is prepared by polymerizing 1,1-difluoroethylene monomer and N,N-dimethylmorpholine ester cyclovinyl monomer. The vinylidene fluoride copolymer has good adhesion and alkali resistance. The morpholine ester ring structure will be hydrolyzed under the weak alkaline conditions of the positive electrode material of the ternary lithium battery to produce carboxyl and hydroxyl groups, which can neutralize the alkali in the system, thereby reducing the gel phenomenon in the positive electrode slurry.

[0005] Although modified PVDF can alleviate the gelation problem of high-nickel ternary cathode material slurry to a certain extent, when the nickel content of the ternary cathode material exceeds 80% (accounting for the total mass of nickel, cobalt and manganese elements), the slurry prepared with modified PVDF as a binder is still prone to gelation, and the fluorine-containing problem has not been solved. Therefore, the development of a positive electrode binder that can avoid the gelation of the positive electrode slurry and does not contain fluorine is an urgent problem to be solved in this field. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a non-fluorine positive electrode binder and a preparation method and application thereof. The non-fluorine positive electrode binder includes a combination of a first polymer and a second polymer that do not contain fluorine, which completely solves the problem that the current application of PVDF in high-nickel ternary batteries easily causes slurry gel. It is environmentally friendly and has excellent dispersibility and adhesion, effectively improving the performance of positive electrode sheets and lithium-ion batteries.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a non-fluorine positive electrode binder, wherein the non-fluorine positive electrode binder comprises a combination of a first polymer and a second polymer.

[0009] The polymerized monomers of the first polymer include the following components in parts by mass:

[0010] Acrylonitrile 80-90 parts

[0011] 5-10 parts of the first acrylic monomer

[0012] 1-5 parts of the first functional monomer.

[0013] The polymerized monomers of the second polymer include the following components in parts by mass:

[0014]

[0015] In the non-fluorine positive electrode binder provided by the present invention, the first polymer is an acrylonitrile multipolymer, and its polymerization monomer is mainly acrylonitrile, and includes a specific amount of a first acrylic ester monomer and a first functional monomer, giving it excellent dispersion performance; the second polymer is an acrylic ester multipolymer, and the polymerization monomer is mainly a second acrylic ester monomer, and includes a specific amount of acrylonitrile, vinyl hydrocarbon monomers and second functional monomers, which helps to improve the bonding performance of the non-fluorine positive electrode binder. The non-fluorine positive electrode binder does not contain any fluorine element. When used in a high-nickel ternary positive electrode system, it avoids the situation that the PVDF molecular chain will remove the HF molecule in a strong alkaline environment, and form continuous double bonds on the molecular chain, and the double bond breaks and cross-links with other molecular chains, thereby completely avoiding the phenomenon of gelation of the slurry, so that the non-fluorine positive electrode binder has excellent coating performance and processability when used to prepare positive electrode slurry and positive electrode sheets; moreover, the cost of the non-fluorine positive electrode binder is low, and it has obvious cost advantages relative to PVDF. It does not belong to the fluorine chemical industry, avoids serious pollution to the environment, and is more environmentally friendly. At the same time, through the design and synergistic compounding of the first polymer and the second polymer formed by the polymerization of specific monomers, the non-fluorine positive electrode binder has good dispersibility for the positive electrode active material and the conductive agent, high bonding strength with the current collector (aluminum foil), and suitable hardness and excellent flexibility, so that the positive electrode sheet containing it has excellent bonding strength and stability, and the performance of the manufactured lithium-ion battery is better.

[0016] In the polymerization monomers of the first polymer, the mass fraction of acrylonitrile is 80-90 parts, for example, it can be 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, 86 parts, 87 parts, 88 parts or 89 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0017] The mass fraction of the first acrylic ester monomer is 5-10 parts, for example, it can be 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts or 9.5 parts, as well as specific values ​​between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0018] The mass fraction of the first functional monomer is 1-5 parts, for example, it can be 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0019] Among the polymerized monomers of the second polymer, the mass fraction of the second acrylic ester monomer is 60-75 parts, for example, it can be 61 parts, 63 parts, 65 parts, 67 parts, 69 parts, 70 parts, 72 parts or 74 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0020] The mass parts of acrylonitrile are 10-15 parts, for example, 10.5 parts, 11 parts, 11.5 parts, 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts or 14.5 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.

[0021] The mass parts of the vinyl hydrocarbon monomer are 10-20 parts, for example, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts or 19 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0022] The mass fraction of the second functional monomer is 1-5 parts, for example, it can be 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0023] Preferably, the first acrylic ester monomer and the second acrylic ester monomer each independently include any one of (meth) acrylate, hydroxyalkyl (meth) acrylate, sulfonalkyl (meth) acrylate, aminoalkyl (meth) acrylate, glycidyl (meth) acrylate, aryl (meth) acrylate, polyethylene glycol mono (meth) acrylate, acetamido acrylate, cyanoacrylate, alkenyl (meth) acrylate, or a combination of at least two thereof.

[0024] In the present invention, the "alkyl (meth)acrylate" includes alkyl acrylate and / or alkyl methacrylate; other similar expressions have similar meanings and are not described one by one.

[0025] Preferably, the first acrylic ester monomer and the second acrylic ester monomer each independently include any one of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hexadecyl (meth)acrylate, sulfopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate, methyl acetamidoacrylate, cyanoacrylate, and vinyl (meth)acrylate, or a combination of at least two thereof.

[0026] Preferably, the first acrylic acid ester monomer and the second acrylic acid ester monomer each independently include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, phenyl methacrylate, lauryl acrylate (dodecyl acrylate), 2-ethylethyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-ethylhexyl acrylate, hexadecyl acrylate, polyethylene glycol monomethacrylate, sulfopropyl acrylate, dimethylaminoethyl acrylate, diethylaminoethyl acrylate, tert-butylaminoethyl acrylate, vinyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, any one or a combination of at least two of ester, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, sulfopropyl methacrylate, 2-ethylethyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate (dodecyl methacrylate), 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate, polyethylene glycol monoacrylate, dimethylaminoethyl methacrylate, diethylaminoethyl methacrylate, tert-butylaminoethyl methacrylate, vinyl methacrylate, benzyl methacrylate, phenyl methacrylate, hexadecyl methacrylate, methyl α-acetamidoacrylate, and cyanoacrylate.

[0027] Preferably, the first functional monomer and the second functional monomer independently include any one of (meth)acrylic acid, acrylamide monomers, itaconic acid, maleic anhydride, dimethyl maleate, and vinyl acetate monomers, or a combination of at least two thereof.

[0028] Preferably, the vinyl acetate monomers include vinyl acetate and / or methoxyvinyl acetate.

[0029] Preferably, the first functional monomer and the second functional monomer independently include any one of methacrylic acid, acrylic acid, and acrylamide, or a combination of at least two of them.

[0030] Preferably, the polymerization monomers of the first polymer and the second polymer respectively include specific amounts of the first functional monomer and the second functional monomer, which can improve the bonding properties of the acrylonitrile multipolymer (first polymer) and the acrylate multipolymer (second polymer), enhance the bonding strength between the positive electrode material composition and the current collector, and thereby improve the bonding strength and stability of the positive electrode sheet.

[0031] Preferably, the vinyl hydrocarbon monomer is a vinyl aromatic hydrocarbon monomer, which has a large steric hindrance, which helps to improve the dispersion effect of the second polymer and the non-fluorine positive electrode binder, improve the dispersibility of the non-fluorine positive electrode binder in the positive electrode slurry to the positive electrode active material and the conductive agent, and give the positive electrode plate more excellent comprehensive performance.

[0032] Preferably, the vinyl hydrocarbon monomer includes any one of substituted or unsubstituted styrene and substituted or unsubstituted naphthylene vinyl, or a combination of at least two thereof.

[0033] The substituted substituents are each independently selected from C1-C24 (e.g., C2, C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, C20, or C22, etc.) straight or branched alkyl, C3-C24 (e.g., C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, C20, or C22, etc.) cycloalkyl, C7-C24 (e.g., C8, C9, C10, C12, C14, C16, C18, C20, or C22, etc.) C9, C10, C12, C14, C16, C18, C20 or C22, etc.) aralkyl, C2-C24 (e.g., C3, C4, C5, C6, C7, C8, C9, C10, C12, C14, C16, C18, C20 or C22, etc.) alkenyl, C6-C24 (e.g., C6, C9, C10, C12, C14, C16, C18, C20 or C22, etc.) aryl, or a combination of at least two of them.

[0034] Preferably, the vinyl hydrocarbon monomer includes any one or a combination of at least two of styrene, α-methylstyrene, vinyltoluene, 2,4-dimethylstyrene, ethylstyrene, isopropylstyrene, butylstyrene, phenylstyrene, cyclohexylstyrene, benzylstyrene, crotonylbenzene, divinylbenzene, divinyltoluene, divinylxylene, trivinylbenzene, and vinylnaphthalene, and styrene is more preferred.

[0035] Preferably, the first polymer and the second polymer are independently prepared by emulsion polymerization.

[0036] Preferably, the emulsion polymerization is carried out in the presence of an initiator, a surfactant and a solvent.

[0037] It should be noted that the first polymer and the second polymer are both prepared by emulsion polymerization, and the types and amounts of initiators, surfactants, and solvents used in the emulsion polymerization are the same or different, and the process parameters (temperature, time, atmosphere) are the same or different.

[0038] Preferably, the initiator is a water-soluble initiator.

[0039] Preferably, the initiator comprises any one of hydrogen peroxide, peracetic acid, persulfate, and redox initiator, or a combination of at least two thereof.

[0040] Preferably, the oxidant in the redox initiator comprises hydroperoxide and / or persulfate.

[0041] Preferably, the persulfate includes any one of ammonium persulfate, potassium persulfate, sodium persulfate, or a combination of at least two of them.

[0042] Preferably, the reducing agent in the redox initiator includes any one of divalent iron salts, sodium sulfite, sodium bisulfite, alcohol, and dimethylaniline, or a combination of at least two thereof.

[0043] Preferably, based on 100 parts by mass of the polymerized monomer, the mass of the initiator is 0.5-2 parts, for example, it can be 0.6 parts, 0.8 parts, 1 parts, 1.1 parts, 1.3 parts, 1.5 parts, 1.7 parts or 1.9 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] Preferably, the surfactant is selected from any one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants, or a combination of at least two thereof.

[0045] Preferably, the anionic surfactant includes any one of carboxylic acid, carboxylate, organic sulfuric acid, organic sulfate, carboxymethylation product salt, organic sulfonic acid, sulfonate, phosphate, or a combination of at least two thereof, illustratively including but not limited to: sodium dodecyl sulfate, sodium octadecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dioctyl succinate sulfonate, sodium fatty alcohol ether sulfate, sulfonate of ethoxylated fatty acid methyl ester, sodium α-olefin sulfonate, sodium secondary alkyl sulfonate, alcohol ether carboxylates, alcohol ether phosphates, lauryl alcohol ether phosphate, isooctyl alcohol ether phosphate, or a combination of at least two thereof.

[0046] Preferably, the cationic surfactant includes a quaternary ammonium salt surfactant and / or an amine salt surfactant, illustratively including but not limited to: didodecyl dimethyl-polyamine-diquaternary ammonium salt, N-dodecyl diquaternary ammonium salt, dodecyl dimethyl benzyl ammonium chloride, polydimethyl diallyl ammonium chloride, dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium bromide, hexadecyl trimethyl ammonium chloride, dodecylbenzenesulfonic acid triethanolamine salt of any one or a combination of at least two.

[0047] Preferably, the amphoteric surfactant includes any one of carboxylic acid type amphoteric surfactant, sulfate type amphoteric surfactant, sulfonate type amphoteric surfactant, phosphate type amphoteric surfactant, or a combination of at least two thereof, illustratively including but not limited to: any one of polyalkyl betaine, dodecyl dihydroxyethyl betaine, dodecyl dimethyl betaine, tetradecyl dihydroxyethyl amine oxide, lauryl dimethyl amine oxide, dodecyl dihydroxyethyl amine oxide, hexadecyl dihydroxyethyl amine oxide, dodecyl amide propyl dimethyl amine oxide, polyoxyethylene ether phosphate, and alkyl alcohol amide phosphate, or a combination of at least two thereof.

[0048] Preferably, the nonionic surfactant includes an oxyalkylene addition nonionic surfactant and / or a polyol type nonionic surfactant, illustratively including but not limited to: decyl alcohol polyoxyethylene ether, bisalkylphenol polyoxyethylene ether, polyoxyethylene ether siloxane, bisalkyl alcohol polyoxyethylene ether, octylphenol polyoxyethylene ether, polyoxyethylene fatty acid ester, isomeric undecanol polyoxyethylene ether, isomeric tridecanol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sorbitan trioleate, sorbitan monooleate, polyoxyethylene sorbitan monooleate, fatty acid polyethylene glycol ester, any one or a combination of at least two thereof.

[0049] Preferably, based on 100 parts by mass of the polymerized monomer, the mass of the surfactant is 0.5-5 parts, for example, it can be 0.6 parts, 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0050] Preferably, the solvent comprises water.

[0051] Preferably, based on 100 parts by mass of the polymerized monomer, the mass of the solvent is 100-200 parts, for example, it can be 110 parts, 120 parts, 130 parts, 140 parts, 150 parts, 160 parts, 170 parts, 180 parts or 190 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] In a preferred technical solution, the raw materials for preparing the first polymer include the following components in parts by mass:

[0053]

[0054] In a preferred technical solution, the raw materials for preparing the second polymer include the following components in parts by mass:

[0055]

[0056]

[0057] The first initiator and the second initiator are the same or different and have the same type range as the initiators described above.

[0058] The first surfactant and the second surfactant are the same or different and have the same type range as the surfactants described above.

[0059] The first solvent and the second solvent are the same or different and have the same type range as the surfactant described above.

[0060] Preferably, the temperature of the emulsion polymerization is 50-100°C, for example, it can be 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range, and 50-80°C is further preferred.

[0061] Preferably, the emulsion polymerization time is 2-24 h, for example, it can be 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 12 h, 15 h, 16 h, 18 h, 20 h or 22 h, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] Preferably, the emulsion polymerization is carried out in a protective atmosphere, and the protective atmosphere is preferably any one of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere, or a combination of at least two of them.

[0063] Preferably, the emulsion polymerization is carried out under stirring conditions.

[0064] Preferably, the stirring speed is 50-300 rpm, for example, it can be 60 rpm, 80 rpm, 100 rpm, 120 rpm, 150 rpm, 180 rpm, 200 rpm, 220 rpm, 250 rpm or 280 rpm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0065] Illustratively, the method for preparing the first polymer includes: adding a surfactant and part of the solvent to a reaction device, mixing the remaining solvent, acrylonitrile, a first acrylic ester monomer and a first functional monomer to obtain material A; adding an initiator to the reaction device under a protective atmosphere and stirring conditions, and adding material A to carry out a polymerization reaction to obtain an emulsion of the first polymer.

[0066] Preferably, the reaction device is a reactor.

[0067] Preferably, the material A is added dropwise.

[0068] Preferably, the method for preparing the first polymer specifically comprises the following steps:

[0069] (S1) adding a surfactant and part of the solvent into a reaction kettle, mixing the remaining solvent, acrylonitrile, the first acrylic ester monomer and the first functional monomer and adding the mixture into a dropping funnel;

[0070] (S2) Nitrogen is introduced into the reactor to replace the air for 10-30 minutes, and the flow rate of nitrogen is controlled at 1-10m 3 / h;

[0071] (S3) turning on heating and stirring, the stirring speed is 50-250 rpm;

[0072] (S4) When the temperature in the reactor reaches 50-65°C, add the initiator, open the dropping funnel and start the dropwise addition reaction for 4-6 hours;

[0073] (S5) After the dropwise addition is completed, the temperature is raised to 65-75° C. and the reaction is continued with stirring for 2-4 hours;

[0074] (S6) Cooling to below 30°C and filtering to obtain an emulsion of the first polymer.

[0075] Preferably, in step (S2), nitrogen is introduced to replace the air for 20-30 minutes.

[0076] Since oxygen in the air has the function of inhibiting polymerization, it will cause the reaction induction period to become longer and reduce the polymerization efficiency in the polymerization reaction. By adopting the above preferred technical solution, after nitrogen is introduced, nitrogen can replace oxygen, reduce the oxygen content in the reaction system, and increase the reaction rate.

[0077] Preferably, in step (S2), the flow rate of nitrogen is controlled to be 4-8m 3 / h.

[0078] The adoption of the above preferred technical scheme is conducive to the smooth progress of the polymerization reaction; if the flow rate of nitrogen is too small, the air replacement effect in the reactor is not obvious, and there is still a lot of oxygen in the reaction system, which has an inhibitory effect on the reaction; if the flow rate of nitrogen is too large, it will bring out some monomers and solvents, change the concentration of monomers in the reaction system, not only affecting the polymerization reaction, but also wasting monomers and increasing costs.

[0079] Preferably, in step (S3), the stirring speed is 100-150 rpm; if the stirring rate is too slow, the generated polymer particles will stick together; if the stirring rate is too fast, the stabilizing effect of the polymer emulsion will be destroyed, not only causing the primary core to be non-uniform, but also causing the polymer particles to agglomerate with each other in the later stage.

[0080] Preferably, the initiator can be added all at once or in batches; preferably, in step (S4), the initiator is added when the temperature in the reactor reaches 55-62°C; in step (S5), the initiator is added when the temperature in the reactor reaches 67-72°C.

[0081] Illustratively, the method for preparing the second polymer includes: adding a surfactant and part of the solvent to a reaction device, mixing the remaining solvent, a second acrylate monomer, acrylonitrile, a vinyl hydrocarbon monomer and a second functional monomer to obtain material B; adding an initiator to the reaction device under a protective atmosphere and stirring conditions, and adding material B to carry out a polymerization reaction to obtain an emulsion of the second polymer.

[0082] Preferably, the reaction device is a reactor.

[0083] Preferably, the material B is added dropwise.

[0084] Preferably, the method for preparing the second polymer specifically comprises the following steps:

[0085] (T1) Add some solvent to the reactor and introduce nitrogen to replace the air for 10-30 minutes. The flow rate of nitrogen is controlled at 1-10m 3 / h, turn on heating and stirring, the stirring speed is 50-250rpm;

[0086] (T2) during the temperature rising period, the remaining solvent, the second acrylic ester monomer, acrylonitrile, the vinyl hydrocarbon monomer and the second functional monomer are mixed and added to the dropping funnel;

[0087] (T3) When the temperature in the reactor reaches 65-75°C, add some initiator and open the dropping funnel to start the dropwise reaction for 3-5 hours;

[0088] (T4) After the addition is completed, the temperature is continued to rise to 70-80°C, and the remaining initiator is added and the reaction is continued with stirring for 4-6 hours;

[0089] (T5) Cooling to below 30°C and filtering to obtain an emulsion of the second polymer.

[0090] Preferably, in step (T1), nitrogen is introduced to replace the air for 20-30 minutes.

[0091] Since oxygen in the air has the function of inhibiting polymerization, it will cause the reaction induction period to become longer and reduce the polymerization efficiency in the polymerization reaction. By adopting the above preferred technical solution, after nitrogen is introduced, nitrogen can replace oxygen, reduce the oxygen content in the reaction system, and increase the reaction rate.

[0092] Preferably, in step (T1), the flow rate of nitrogen is controlled to be 4-8m 3 / h; if the flow rate of the nitrogen introduced is too small, the air replacement effect in the reactor is not obvious, and there is still a lot of oxygen in the reaction system, which has an inhibitory effect on the reaction; if the flow rate of the nitrogen introduced is too large, it will bring out some monomers and solvents, changing the concentration of monomers in the reaction system, which not only affects the polymerization reaction, but also wastes monomers and increases costs.

[0093] Preferably, in step (T1), the stirring speed is 100-150 rpm; if the stirring rate is too slow, the generated polymer particles will stick together; if the stirring rate is too fast, the stabilizing effect of the polymer emulsion will be destroyed, not only causing the primary core to be non-uniform, but also causing the polymer particles to agglomerate with each other in the later stage.

[0094] Preferably, in step (T3), when the temperature in the reactor reaches 68-72°C, 60% of the initiator is added; in step (T4), when the temperature in the reactor reaches 75-78°C, the remaining initiator is added.

[0095] Preferably, the weight average molecular weight of the first polymer is 400,000-800,000, for example, it can be 420,000, 450,000, 480,000, 500,000, 520,000, 550,000, 580,000, 600,000, 620,000, 650,000, 680,000, 700,000, 720,000, 750,000 or 780,000, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0096] Preferably, the weight average molecular weight of the second polymer is 300,000-900,000, for example, it can be 350,000, 400,000, 450,000, 500,000, 550,000, 600,000, 650,000, 700,000, 750,000, 800,000 or 850,000, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0097] Preferably, the mass ratio of the first polymer to the second polymer is 1:(0.4-2.4), for example, it can be 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.1 or 1:2.3, etc., more preferably 1:(0.6-1.5), and even more preferably 1:(1-1.5).

[0098] In a second aspect, the present invention provides a method for preparing the non-fluorine positive electrode binder as described in the first aspect, the preparation method comprising: mixing an emulsion of a first polymer with an emulsion of a second polymer and then drying and powdering them to obtain the non-fluorine positive electrode binder.

[0099] Preferably, the dry powder making method comprises any one of spray drying, fluidized bed drying, flash drying, microwave drying or a combination of at least two thereof, and spray drying is further preferred.

[0100] Preferably, the particle size of the non-fluorine positive electrode binder is 40-60 μm, for example, it can be 42 μm, 45 μm, 48 μm, 50 μm, 52 μm, 55 μm or 58 μm, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0101] In a third aspect, the present invention provides a positive electrode material composition, which comprises a combination of the non-fluorine positive electrode binder, the positive electrode active material and the conductive agent as described in the first aspect.

[0102] Preferably, the positive electrode active material comprises a ternary positive electrode active material.

[0103] Preferably, the conductive agent includes any one of conductive carbon black, conductive graphite, Ketjen black, acetylene black, carbon nanotubes, carbon fibers, graphene, and conductive polymers, or a combination of at least two thereof.

[0104] Preferably, the positive electrode material composition comprises the following components in parts by mass:

[0105] 90-99 parts of positive electrode active material

[0106] Conductive agent 0.5-5 parts

[0107] 0.5-5 parts of non-fluorine positive electrode binder.

[0108] Among them, the mass parts of the positive electrode active material are 90-99 parts, for example, it can be 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, 97 parts or 98 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0109] The mass proportion of the conductive agent is 0.5-5 parts, for example, it can be 0.8 parts, 1.0 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0110] The mass fraction of the non-fluorine positive electrode binder is 0.5-5 parts, for example, it can be 0.8 parts, 1.0 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0111] In a fourth aspect, the present invention provides a positive electrode plate, comprising a current collector and a coating disposed on the current collector, wherein the material of the coating comprises the positive electrode material composition as described in the third aspect.

[0112] Preferably, the current collector is aluminum foil.

[0113] Preferably, the method for preparing the positive electrode sheet comprises: uniformly mixing the positive electrode material composition with a solvent to obtain a slurry; coating the slurry on a current collector, and drying to obtain the positive electrode sheet.

[0114] Preferably, the moisture content of the positive electrode sheet after drying is ≤300 ppm.

[0115] As a preferred technical solution of the present invention, the slurry containing the non-fluorine positive electrode binder has suitable viscosity and excellent viscosity stability. The non-fluorine positive electrode binder has a good dispersion effect on the positive electrode active material and the conductive agent. The initial viscosity is 4515-4608 mPa·s, the viscosity of the slurry after 24 hours is 4546-4758 mPa·s, the viscosity after 48 hours is 4752-4903 mPa·s, and the viscosity after 72 hours is 5012-5116 mPa·s. There is no phenomenon of increasing viscosity over time, and the slurry has excellent coating performance and processability.

[0116] In a fifth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the fourth aspect.

[0117] The lithium-ion battery also includes a negative electrode plate, an electrolyte and a separator.

[0118] Compared with the prior art, the present invention has the following beneficial effects:

[0119] (1) The non-fluorine positive electrode binder provided by the present invention does not contain any fluorine element, which completely solves the problem that PVDF is easily prone to slurry gel when used in high-nickel ternary materials. When used to prepare positive electrode plates, it has excellent coating performance and processability; moreover, the non-fluorine positive electrode binder is low in cost and does not belong to the fluorine chemical industry, thus avoiding pollution to the environment and being more environmentally friendly.

[0120] (2) The present invention designs and synergistically compounds the first polymer and the second polymer formed by polymerization of specific monomers, so that the non-fluorine positive electrode binder has good dispersibility for the positive electrode active material and the conductive agent, high binding force with the current collector, and suitable hardness and excellent flexibility, so that the positive electrode sheet containing it has excellent bonding force and stability, and the performance of the manufactured lithium-ion battery is better.

[0121] (3) The positive electrode sheet containing the non-fluorine positive electrode binder has high bonding force, with cohesion ≥ 20.35N, cohesive strength ≥ 1044.8N / m, interface peeling force ≥ 5.75N, and interface peeling strength ≥ 287N / m. The improvement of the bonding force and stability of the positive electrode sheet also effectively improves the electrochemical performance of the lithium-ion battery, making the internal resistance less than 47mΩ, the first efficiency ≥ 86.1%, the capacity retention rate high, and the cycle performance and service life significantly improved. DETAILED DESCRIPTION

[0122] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0123] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0124] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.

[0125] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0126] In the following specific embodiments of the present invention, the materials used are all commercially available products.

[0127] Preparation Example 1

[0128] The first polymer A1, the raw materials for preparation include the following components by weight:

[0129]

[0130] The specific preparation method comprises the following steps:

[0131] (S1) adding 100 parts of deionized water and 0.55 parts of sodium lauryl sulfate into a reaction kettle; then mixing 50 parts of deionized water, 88 parts of acrylonitrile, 10 parts of n-butyl acrylate and 2 parts of acrylamide and placing the mixture into a dropping funnel;

[0132] (S2) Nitrogen was introduced into the reactor to replace the air for 30 min, and the flow rate of nitrogen was controlled at 6 m 3 / h;

[0133] (S3) turning on a water bath for heating and stirring at a stirring speed of 100 rpm;

[0134] (S4) When the temperature in the reactor reaches 60° C., add 1 portion of potassium persulfate, open the dropping funnel and start the dropwise addition reaction for 5 hours;

[0135] (S5) After the dropwise addition is completed, the temperature is continued to rise to 70° C. and the reaction is stirred for 3 h;

[0136] (S6) Cooling to below 30°C and filtering to obtain an emulsion of the first polymer A1.

[0137] Preparation Examples 2-3, Comparative Preparation Examples 1-3

[0138] The raw materials and amounts used in the preparation of the first polymers A2-A3 and AD1-AD3 are shown in Table 1. The amounts of each component in Table 1 are all in "parts", and "--" represents that the component is not added; the preparation method is the same as that in Preparation Example 1.

[0139] Table 1

[0140] A1 A2 A3 AD1 AD2 AD3 Acrylonitrile 88 90 85 98 90 100 n-Butyl acrylate 10 7 10 -- 10 -- Acrylamide 2 3 5 2 -- -- Potassium Persulfate 1 1 1 1 1 1 Sodium Lauryl Sulfate 0.55 0.55 0.55 0.55 0.55 0.55 Deionized water 150 150 150 150 150 150

[0141] Preparation Example 4

[0142] The second polymer B1, the raw materials for preparation include the following components by mass:

[0143]

[0144]

[0145] The specific preparation method comprises the following steps:

[0146] (T1) In a reactor, 50 parts of deionized water and 0.55 parts of sodium dodecylbenzene sulfonate were added, and nitrogen was introduced to replace the air for 30 minutes. The flow rate of nitrogen was controlled at 6m 3 / h, turn on the water bath to heat and stir, the stirring speed is 100rpm;

[0147] (T2) during the temperature rise period, the remaining 100 parts of deionized water, 70 parts of n-butyl acrylate, 10 parts of acrylonitrile, 15 parts of styrene and 5 parts of acrylamide were mixed and added to the dropping funnel;

[0148] (T3) When the temperature in the reactor reaches 68°C, add 0.6 parts of sodium persulfate and open the dropping funnel to start the dropwise addition reaction for 4 hours;

[0149] (T4) After the addition is completed, the temperature is continued to rise to 75° C., the remaining 0.4 parts of sodium persulfate is added and the reaction is stirred for 5 hours;

[0150] (T5) Cooling to below 30°C and filtering to obtain an emulsion of the second polymer B1.

[0151] Preparation Examples 5-6, Comparative Preparation Examples 4-8

[0152] The raw materials and amounts used in the preparation of the second polymers B2-B3 and BD1-BD5 are shown in Table 2. The amounts of each component in Table 2 are all measured in "parts", and "--" represents that the component is not added; the preparation method is the same as that of Preparation Example 4.

[0153] Table 2

[0154]

[0155]

[0156] Example 1

[0157] A non-fluorine positive electrode binder is composed of a first polymer A1 and a second polymer B1, and the mass ratio of the first polymer A1 and the second polymer B1 is 1:1. The preparation method is as follows:

[0158] The emulsion of the first polymer A1 (Preparation Example 1) and the emulsion of the second polymer B1 (Preparation Example 4) were mixed at a solid content ratio of 1:1, and then dried and powdered using a spray dryer. The inlet temperature of the spray dryer was 170°C, the outlet temperature was 90°C, and the atomizer frequency was 230 Hz to obtain the non-fluorine positive electrode binder.

[0159] Examples 2-3, Comparative Examples 1-11

[0160] A non-fluorine positive electrode binder, composed of a first polymer and a second polymer, which is different from Example 1 in that the types and mass ratios of the first polymer and the second polymer are different, as shown in Table 3; in Table 3, "mass ratio" represents the mass ratio (solid content) of the first polymer to the second polymer, and "--" represents that the component is not added / the ratio does not exist; the preparation method of each non-fluorine positive electrode binder is the same as that in Example 1.

[0161] Table 3

[0162]

[0163]

[0164] Application Example 1-3, Comparative Application Example 1-12

[0165] A positive electrode sheet, comprising a current collector (aluminum foil) and a coating disposed on the current collector, wherein the material of the coating is a positive electrode material composition; the positive electrode material composition comprises the following components in parts by mass:

[0166]

[0167] Among them, the binder is the non-fluorine positive electrode binder provided in Examples 1-3 and Comparative Examples 1-11, and PVDF5130 in Comparative Example 12.

[0168] The preparation method of the positive electrode sheet is as follows: the positive electrode material composition of the formula amount is fully mixed with the solvent N-methylpyrrolidone (NMP) to prepare a positive electrode slurry with a solid content of about 72%; the positive electrode slurry is coated on the current collector aluminum foil, and after drying and rolling, the positive electrode sheet is obtained.

[0169] A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, specifically a 503040-550 mAh battery, wherein the positive electrode sheet is the above-mentioned positive electrode sheet; the preparation method of the lithium-ion battery is as follows:

[0170] (1) Preparation of positive electrode sheet: as described above;

[0171] (2) Preparation of negative electrode sheet: The negative electrode slurry includes the following components by weight:

[0172]

[0173] A double planetary mixer is used to prepare the negative electrode slurry. The thickener CMC according to the above formula is dissolved in deionized water, and then conductive carbon black Super P Li and graphite are added respectively. After stirring and dispersing evenly, SBR is added and mixed evenly to obtain a negative electrode slurry with a solid content of 48%. The negative electrode slurry is coated on the current collector copper foil, and after drying and rolling, a negative electrode sheet is obtained;

[0174] (3) Diaphragm: commercially available Celgard2312 diaphragm;

[0175] (4) Assembly of lithium-ion battery: The positive electrode sheet, the separator and the negative electrode sheet are stacked in sequence and then wound to obtain a battery cell, the battery cell is loaded into a 503040 aluminum-plastic film, an electrolyte (1 mol / L LiPF6, the solvent is a mixed solvent of ethylene carbonate EC: ethyl methyl carbonate EMC: diethyl carbonate DEC = 3:5:2) is injected, and hot pressing and sealing are performed to obtain the lithium-ion battery.

[0176] Performance Test:

[0177] 1. Viscosity test of positive electrode slurry

[0178] The viscosity of the prepared positive electrode slurry was directly tested using an SNB-1 digital viscometer at a test temperature of 25°C. The initial viscosity after preparation, and the viscosity after 24h, 48h, and 72h were tested respectively. The results are shown in Table 4.

[0179] Table 4

[0180]

[0181] According to the test results in Table 4, compared with the conventional PVDF binder in Comparative Example 12, the positive electrode slurry prepared by the non-fluorine positive electrode binder provided by the present invention has no significant difference in the initial viscosity value; as the placement time increases, the viscosity of the positive electrode slurry using the non-fluorine positive electrode binder provided by Examples 1-3 does not change significantly, with an initial viscosity of 4515-4608 mPa·s, a viscosity of 4546-4758 mPa·s after 24 hours, a viscosity of 4752-4903 mPa·s after 48 hours, and a viscosity of 5012-5116 mPa·s after 78 hours, and a significant improvement in viscosity stability. In the non-fluorine positive electrode binders of Comparative Examples 1-11, since the compounding of the two specific polymers of the present invention is not used, the dispersibility and stability of the positive electrode slurry containing it are not good, and there will be a significant increase in viscosity after being placed for a period of time.

[0182] 2. Adhesion test of positive electrode

[0183] The adhesion test of the positive electrode sheet was carried out by using a GBH-1 tensile testing machine and a 180° tape peeling method. The test sample size was 20 mm × 100 mm, and the tensile rate was 50 mm / min. The specific test method was based on the test method for peeling strength of adhesive tape in GB / T 2792-2014. The results are shown in Table 5.

[0184] Table 5

[0185]

[0186]

[0187] According to the test results in Table 5, compared with the conventional PVDF binder in Comparative Example 12, the positive electrode plate prepared by the non-fluorine positive electrode binder provided by the present invention has higher bonding force, and its cohesive force is 20.35-21.65N, the cohesive strength is 1044.88-1117.73N / m, the interface peeling force is 5.75-6.16N, and the interface peeling strength is 287.28-307.8N / m. The bonding force and stability of the plate are significantly improved, and the improvement rate can reach 10%-30%.

[0188] 3. Electrochemical performance test of lithium-ion batteries

[0189] The electrochemical performance of the prepared lithium-ion battery was tested using the Blue Electric Battery Test System. The specific method is as follows:

[0190] (A) Internal resistance

[0191] (1) Charge to 3.4V using 0.03C, charging time is 240min;

[0192] (2) Charge to 3.75V using 0.1C, charging time is 420min;

[0193] (3) Charge to 4.2V using 0.5C, with a cut-off current of 0.02C;

[0194] (4) Discharge to 3.0 V using 0.5C and record the discharge capacity;

[0195] (5) Charge to 4.2V using 0.5C, with a cut-off current of 0.02C;

[0196] (6) Discharge to 3.0 V using 0.5C and record the discharge capacity;

[0197] (7) Charge to 50% SOC using 0.5C and test the internal resistance.

[0198] (B) Initial efficiency

[0199] (1) Charging: 0.5C constant current to 4.2V, 4.2V constant voltage, 0.05C cut-off current, record the charging capacity;

[0200] (2) Discharge: 0.5C constant current discharge to 3V, record the discharge capacity.

[0201] (C) Capacity retention rate

[0202] The capacity retention rate of lithium-ion batteries was tested at different rate conditions of 0.2C / 0.2C, 0.5C / 0.2C, 1C / 0.2C, 2C / 0.2C, and 3C / 0.2C;

[0203] The results are shown in Table 6.

[0204] Table 6

[0205]

[0206]

[0207] According to the test results in Table 6, compared with conventional PVDF binders, the positive electrode sheet prepared by the non-fluorine positive electrode binder provided by the present invention has better bonding force and stability, so that the electrochemical performance of the lithium-ion battery is improved, the internal resistance is 45.7-46.3mΩ, the first efficiency is 86.1-87.2%, and the capacity retention rate under different rate conditions is high. The capacity retention rates of 0.5C / 0.2C, 1C / 0.2C, 2C / 0.2C, and 3C / 0.2C are 96.45-97.12%, 95.31-95.89%, 93.14-93.58%, and 91.31-91.97%, respectively. The comprehensive performance is significantly improved, and the improvement rate of the electrochemical performance is 1.2%-3.3%. The non-fluorine positive electrode binder of comparative example 1-11 does not adopt the compound of two types of polymers polymerized from specific monomers in the present invention, resulting in that it cannot have both good dispersibility and adhesion, and the adhesion and stability of the positive electrode plate are insufficient, resulting in poor electrochemical performance of the lithium-ion battery, which is specifically manifested in high internal resistance and decreased initial efficiency and capacity retention rate.

[0208] The applicant declares that the present invention illustrates the non-fluorine positive electrode binder and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A non-fluorine positive electrode binder, characterized in that: The non-fluorine positive electrode binder comprises a combination of a first polymer and a second polymer; The polymerized monomers of the first polymer include the following components in parts by mass: Acrylonitrile 80-90 parts 5-10 parts of the first acrylic monomer 1-5 parts of the first functional monomer; The polymerized monomers of the second polymer include the following components in parts by mass: The first acrylate monomer and the second acrylate monomer each independently include any one of (meth) acrylate alkyl, (meth) acrylate sulfonalkyl, (meth) acrylate aminoalkyl, (meth) acrylate glycidyl, (meth) acrylate aryl, polyethylene glycol mono (meth) acrylate, acetamido acrylate, cyanoacrylate, alkenyl (meth) acrylate or a combination of at least two thereof; The first functional monomer and the second functional monomer each independently include an acrylamide monomer; The vinyl hydrocarbon monomer includes any one or a combination of at least two of substituted or unsubstituted styrene and substituted or unsubstituted naphthylene vinyl; The mass ratio of the first polymer to the second polymer is 1:(0.4-2.4); The preparation method of the non-fluorine positive electrode binder comprises: mixing an emulsion of a first polymer and an emulsion of a second polymer, and then drying and powdering the mixture to obtain the non-fluorine positive electrode binder.

2. The non-fluorine positive electrode binder according to claim 1, characterized in that: The first acrylic ester monomer and the second acrylic ester monomer each independently include any one of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, benzyl (meth)acrylate, lauryl (meth)acrylate, 2-ethylethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, hexadecyl (meth)acrylate, sulfopropyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, tert-butylaminoethyl (meth)acrylate, methyl acetamidoacrylate, cyanoacrylate, and vinyl (meth)acrylate, or a combination of at least two thereof.

3. The non-fluorine positive electrode binder according to claim 1, characterized in that: The first functional monomer and the second functional monomer include acrylamide.

4. The non-fluorine positive electrode binder according to claim 1, characterized in that: The substituted substituents are each independently selected from any one or a combination of at least two of C1-C24 straight or branched alkyl, C3-C24 cycloalkyl, C7-C24 aralkyl, C2-C24 alkenyl, and C6-C24 aryl.

5. The non-fluorine positive electrode binder according to claim 1, characterized in that: The first polymer and the second polymer are independently prepared by emulsion polymerization.

6. The non-fluorine positive electrode binder according to claim 5, characterized in that: The emulsion polymerization is carried out in the presence of an initiator, a surfactant and a solvent.

7. The non-fluorine positive electrode binder according to claim 6, characterized in that: The initiator includes any one of hydrogen peroxide, peracetic acid, and persulfate, or a combination of at least two of them.

8. The non-fluorine positive electrode binder according to claim 6, characterized in that: The initiator includes a redox initiator.

9. The non-fluorine positive electrode binder according to claim 6, characterized in that: Based on 100 parts by weight of the polymerizable monomer, the weight of the initiator is 0.5-2 parts.

10. The non-fluorine positive electrode binder according to claim 6, characterized in that: The surfactant is selected from any one of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants, or a combination of at least two thereof.

11. The non-fluorine positive electrode binder according to claim 6, characterized in that: Based on 100 parts by weight of the polymerized monomer, the weight of the surfactant is 0.5-5 parts.

12. The non-fluorine positive electrode binder according to claim 6, characterized in that: The solvent includes water.

13. The non-fluorine positive electrode binder according to claim 6, characterized in that: Based on 100 parts by weight of the polymerized monomer, the weight of the solvent is 100-200 parts by weight.

14. The non-fluorine positive electrode binder according to claim 5, characterized in that: The temperature of the emulsion polymerization is 50-100°C.

15. The non-fluorine positive electrode binder according to claim 14, characterized in that: The temperature of the emulsion polymerization is 50-80°C.

16. The non-fluorine positive electrode binder according to claim 5, characterized in that: The emulsion polymerization time is 2-24h.

17. The non-fluorine positive electrode binder according to claim 1, characterized in that: The mass ratio of the first polymer to the second polymer is 1:(0.6-1.5).

18. A method for preparing a non-fluorine positive electrode binder according to any one of claims 1 to 17, characterized in that: The preparation method comprises: mixing an emulsion of a first polymer and an emulsion of a second polymer, and then drying and powdering the mixture to obtain the non-fluorine positive electrode binder.

19. The preparation method according to claim 18, characterized in that: The dry powder making method includes any one of spray drying, fluidized bed drying, flash drying, microwave drying or a combination of at least two thereof.

20. The preparation method according to claim 18, characterized in that: The particle size of the non-fluorine positive electrode binder is 40-60 μm.

21. A positive electrode material composition, characterized in that: The positive electrode material composition comprises a combination of a non-fluorine positive electrode binder, a positive electrode active material and a conductive agent as described in any one of claims 1 to 17.

22. A positive electrode plate, characterized in that: The positive electrode plate includes a current collector and a coating disposed on the current collector, and the material of the coating includes the positive electrode material composition as claimed in claim 21.

23. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 22.

Citation Information

Patent Citations

  • Binder, positive electrode slurry, preparation method thereof, and lithium-ion battery

    CN109713306A

  • Binder and positive plate and battery comprising same

    CN115188963A

  • Vinylidene fluoride copolymer as well as preparation method and application thereof

    CN115286730A

  • Battery binder, lithium ion battery negative electrode plate, and lithium ion battery

    CN111500228A

  • BINDER, NEGATIVE ELECTRODE SLURRY INCLUDING THE SAME, NEGATIVE ELECTRODE and RECHARGEABLE BATTERY

    CN111864208A